Development of an Online General Biology Open Educational Resource (OER) Laboratory Manual - Dmitry Y. Brogun (American Society for Microbiology, 2021)
ABSTRACT Currently, many academic institutions are using one or more variations of online modalities due to the COVID-19 pandemic, and science educators face a unique challenge with distance-learning laboratories. Many resources to engage students in virtual, interactive laboratory activities exist, but we found that high costs and/or overlooked content left gaps for several topics typically taught in a general, introductory biology course for undergraduate biology majors (e.g., organismal biology). Additionally, resources for an online lab must be identified and curated from multiple sources, requiring intense demands on the instructors’ time. To meet this need and to overcome the financial burden of high-cost lab manuals or software, we developed, piloted, and revised a series of online general biology lab exercises. We have published these exercises as an Open Educational Resource (OER) digital laboratory manual under the Creative Commons License Agreement, and they are accessible online via Manifold, Creative Commons, and the CUNY Academic Works portal.